Novel Targets of SARS-CoV-2 Spike Protein in Human Fetal Brain Development Suggest Early Pregnancy Vulnerability - Varma, Parul; Lybrand, Zane R.; Antopia, Mariah C.; Hsieh, Jenny (Frontiers in Neuroscience, 2021)
Pregnant women are at greater risk of infection by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), because of their altered immunity and strained cardiovascular system. Emerging studies of placenta, embryos, and cerebral organoids suggest that fetal organs including brain could also be vulnerable to coronavirus disease 2019 (COVID-19). Moreover, a case study from Paris has reported transient neurological complications in neonates born to pregnant mothers. However, it remains poorly understood whether the fetal brain expresses cellular components that interact with Spike protein (S) of coronaviruses, which facilitates fusion of virus and host cell membrane and is the primary protein in viral entry. To address this question, we analyzed the expression of known (ACE2, TMPRSS2 and FURIN) and novel (ZDHHC5, GOLGA7 and ATP1A1) S protein interactors in publicly available fetal brain bulk and single cell RNA sequencing datasets. Bulk RNA sequencing analysis across multiple regions of fetal brain spanning 8 weeks post conception (wpc) - 37wpc indicates that two of the known S protein interactors are expressed at low levels with median normalized gene expression values ranging from 0.08-0.06 (ACE2) and 0.01-0.02 (TMPRSS2). However, the third known S protein interactor FURIN is highly expressed (11.1-44.09) in fetal brain. Interestingly, all three novel S protein interactors are abundantly expressed throughout fetal brain development with median normalized gene expression values ranging from 20.38-21.60 (ZDHHC5), 92.47-68.35 (GOLGA7) and 65.45-194.5 (ATP1A1). Moreover, the peaks of expression of novel interactors is around 12-26wpc. Using publicly available single cell RNA sequencing datasets, we further show that novel S protein interactors show higher co-expression with neurons than with neural progenitors and astrocytes. These results suggest that even though two of the known S protein interactors are present at low levels in fetal brain, novel S protein interactors are abundantly present and could play a direct or indirect role in SARS-CoV-2 fetal brain pathogenesis, especially during the 2nd and 3rd trimesters of pregnancy.